THE ROLE OF INTERACTIVE GAMES IN LEARNING ENGLISH - Abdug’ofurov Shohrux Sherali o’g’li; Khaydarova Shoira Toxir qizi (TADQIQOTLAR, 2026)
Abstract: This article discusses the role of interactive games in helping students acquire English, increasing engagement, motivation, and the development of language skills. Resources like Kahoot, Wordwall, Bingo, and Charades are analyzed to be effective classroom tools to make mundane classroom sessions fun and entertaining. The above-mentioned observations make it clear that games encourage increased participation, reduce the hesitancy of learning, and retain memories through the emphasis of core areas of the language skill, like speaking, listening, and vocabulary development.